Hubungan Dukungan Orang Tua dengan Motivasi Belajar Penjas Siswa Kelas Tinggi - Muliadi Muliadi; Firdaus Firdaus; Annida Us Salamah Adz Dzikru (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The problem in this study is the lack of parental support so that it can affect the motivation to learn Physical Education. This study is a quantitative study with a correlation approach that aims to determine the relationship between parental support and physical education learning motivation. The results showed that obtained rx = 0.547 then the relationship between the two variables was classified at the level of relationship in the "medium" category, because it was in the range 0.40 - 0.599 and the rcount value (0.547) was greater (>) rtable value (0.300) which means H0 rejected and Ha accepted. Based on the analysis of the data above, it can open parental support which will have an impact on students' physical education learning motivation. So, increasing parental support will increase students' learning motivation for Physical Education. From these conclusions, the impact resulting from this study is known that good parental support will increase students' physical education learning motivation.